2020
DOI: 10.1002/bjs.11588
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of PERItoneal disease in Stomach Cancer with cytOreductive surgery and hyperthermic intraPEritoneal chemotherapy: PERISCOPE I initial results

Abstract: Background The role of cytoreductive surgery combined with hyperthermic intraperitoneal chemotherapy (HIPEC) in gastric cancer is unknown. This non‐randomized dose‐finding phase I–II study was designed to assess the safety and feasibility of HIPEC, following systemic chemotherapy, in patients with gastric cancer and limited peritoneal dissemination. The maximum tolerated dose of normothermic intraperitoneal docetaxel in combination with a fixed dose of intraperitoneal oxaliplatin was also explored. Methods Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 43 publications
(114 reference statements)
0
20
1
1
Order By: Relevance
“…Hypothesizing that, specifically, patients with limited peritoneal disease seem to benefit from HIPEC, prophylactic HIPEC treatment has been suggested to potentially prevent or postpone peritoneal metastasis [ 16 , 17 ]. However, HIPEC is associated with considerable morbidity [ 18 ] and, preferably, should be restricted to a select group of patients with a very high risk for developing isolated PM. An accurate prediction model to identify these patients at high risk for metachronous isolated PM that might benefit from prophylactic treatment is, therefore, needed.…”
Section: Introductionmentioning
confidence: 99%
“…Hypothesizing that, specifically, patients with limited peritoneal disease seem to benefit from HIPEC, prophylactic HIPEC treatment has been suggested to potentially prevent or postpone peritoneal metastasis [ 16 , 17 ]. However, HIPEC is associated with considerable morbidity [ 18 ] and, preferably, should be restricted to a select group of patients with a very high risk for developing isolated PM. An accurate prediction model to identify these patients at high risk for metachronous isolated PM that might benefit from prophylactic treatment is, therefore, needed.…”
Section: Introductionmentioning
confidence: 99%
“… 25 Recent work comparable with our study, performed in peritoneal metastasis from gastric cancer, has shown substantial treatment-related mortality, with 50% mortality at the highest investigated dose level of docetaxel in combination with oxaliplatin. 26 Furthermore, serious adverse events were reported in 17/25 patients.…”
Section: Discussionmentioning
confidence: 99%
“…An immanent design aspect of this clinical trial is that no control group without HIPEC treatment has been included, which does limit the precise attribution of adverse events to specific parts of the investigated treatment. Furthermore, the heterogeneous patient cohort and surgical treatment may raise legitimate critique in the context of oncological benefits, whereas these circumstances do not interfere with the primary endpoints of this trial (see also van der Kaaij et al 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…The initial results of the PERISCOPE-trial aimed at dosefinding were recently published. Although the amount of serious adverse events in the trial was high (17 out of 25 patients), it was shown that HIPEC with a dose of 50 mg/m 2 intraperitoneal docetaxel appeared to be feasible [100] Survival data from that trial are currently awaited.…”
Section: Gastric Cancermentioning
confidence: 99%